Ultrasound assisted synthesis of nanosized oxide semiconductors/ordered mesoporous carbon nanoarchitectures - Maria Ignat; Liviu Sacarescu; Aurelia Vasile (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2020)
The present work reports the ultrasound assisted synthesis of nanosized oxide semiconductors, as TiO2 (anatase) and Bi2O3 (α-phase)/mesoporous carbon stable architectures exhibiting high photocatalytic activity for organic pollutants degradation. The use of ordered mesoporous carbon with a pore diameter around 5nm and high specific surface area of 1392m2/g was a successful one, providing an ideal support for semiconductor oxide photocatalysts. Thus, by using ultrasound assisted method the photoactive systems for organics removal from waste waters has been obtained.  Due to the presence of the polar oxygenated groups on mesoporous carbon surface, these might stimulate the formation of the stable (nano) architectures, and enhance the interfacial combination of semiconducting oxide nanoparticles with carbon nanostructure. The prepared systems by this way have been characterized by N2-sorption measurements, X-ray diffraction, SEM microscopy and FTIR spectroscopy. A correlation between their structural, textural and morphological properties is related, and the photocatalytic activity of the synthesized materials has been checked for the methyl orange bleaching in liquid phase, under UV light. The photocatalytic performance of the synthesized nanosized oxide semiconductors/ordered mesoporous carbon nanoarchitectures was evaluated by bleacing of Methyl Orange (MO). It was found that the synthesized α-Bi2O3/mesoporous carbon and TiO2/mesoporous carbon composites showed a much higher degradation efficiencies (of 95% and 98%, respectively) as compared to commercial anatase nanoparticles. For the enhanced photocatalytic activity of the composite systems is responsible the synergistic effect as result of mesoporous carbon structure - oxide semiconductor interactions.